Perancangan UI/UX Design Aplikasi Jasa Fotografi Dengan Design Science Research Methodology - Deden Sukma Hendrawan; Mochzen Gito Resmi; Uus Muhammad Husni Tamyiz (Jurnal Bangkit Indonesia, 2022)
Creative industries such as the world of photography have their own color in the technical twists and turns that influence the development of the world of photography. There are many supporting elements in terms of tools and human resources that play a role in the world of photography, the tools needed such as cameras, lenses, tripods, lights, etc. Based on the subject shown, photographic works have different forms and are classified in three subdisciplines, namely the genres of commercial photography, journalism, and art/expression photography. User Interface (UI) is the way programs and users interact. The term user interface is sometimes used instead of the term Human Computer Interaction (HCI) where all aspects of user and computer interaction. User Experience (UX) is a person's perception and response from the use of a product, system, or service. User Experiece (UX) assesses how satisfied and comfortable a person is with a product, system, and service. The method used by the author to design the UI/UX Design of the Photography Reservation Application is the Design Science Research Methodology using the Heuristic Evaluation test. The purpose of this study is to design a UI/UX Design on a photography service reservation application that is integrated with a mobile application to facilitate the process that can be booked or reserved in advance for customers of photography services. The software used to design this UI/UX Design is a Figma application. Keywords— Photography, Design Science Research Methology, Heuristic Evaluation, UI/UX Design, Figma